2017
DOI: 10.18632/oncotarget.19093
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CLC-3 chloride channel reduces the aggressiveness of glioma through inhibiting nuclear factor-κB pathway

Abstract: CLC-3 chloride channel plays important roles on cell volume regulation, proliferation and migration in normal and cancer cells. Recent growing evidence supports a critical role of CLC-3 in glioma metastasis, however, the mechanism underlying is unclear. This study finds that CLC-3 is upregulated in glioma tissues and positively correlated with WHO histological grade. Patients with high CLC-3 expression had an overall shorter survival time, whereas patients with low expression of CLC-3 had a better survival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Blocking chloride channels can lead to the inhibition of cell proliferation and the arrest of cell cycle progression in human laryngeal cancer cells (28). It was reported that ClC-3, the inhibition of which was shown to decrease the aggressiveness of neuroglioma cells by inhibiting the NF-κB pathway, may be a novel therapeutic target and prognostic biomarker in neuroglioma (29). ClC-3 is a potential target for cancer therapy, and we found that it was highly expressed in Hep3B cells.…”
Section: Discussionmentioning
confidence: 53%
“…Blocking chloride channels can lead to the inhibition of cell proliferation and the arrest of cell cycle progression in human laryngeal cancer cells (28). It was reported that ClC-3, the inhibition of which was shown to decrease the aggressiveness of neuroglioma cells by inhibiting the NF-κB pathway, may be a novel therapeutic target and prognostic biomarker in neuroglioma (29). ClC-3 is a potential target for cancer therapy, and we found that it was highly expressed in Hep3B cells.…”
Section: Discussionmentioning
confidence: 53%
“…These modifications are part of the so called “epithelial-mesenchymal transition” (EMT) (see Section 2.2 ), which, although its role in glioma is still controversial, seems to be determinant for the degree of malignancy [ 27 ]. In addition, movement of cells throughout the brain tissue requires cell shape changes and protrusion of invadopodia, probably based on both modifications of the cytoskeleton [ 28 , 29 ] and movements of ions [ 30 , 31 ] and water [ 32 , 33 , 34 ] between the two sides of the plasma membrane. In this Section, we discuss these molecular modifications, while in Section 3 we will discuss possible involvement of EVs in them.…”
Section: Cellular and Molecular Bases Of Glioma Growth And Invasiomentioning
confidence: 99%
“…Taken together, these observations suggest that modifications of volume are critical for invasion and that they depend, at least in part, on ion fluxes and in turn on the expression of ion channels. It has been, for example, reported that CLC-3, one member of CLC voltage-gated chloride channel family, is upregulated in gliomas and correlates with a shorter survival of patients [ 31 ]. Similarly, the chloride intracellular channel 1 (CLIC1) is overexpressed in glioblastoma, with the highest expression in patients with worse prognosis [ 156 ].…”
Section: Cellular and Molecular Bases Of Glioma Growth And Invasiomentioning
confidence: 99%
“…Specifically, SLP2 was fond to be markedly upregulated in glioma cells and glioma specimens. The up-regulation of SLP2 was shown to be significantly correlated with the World Health Organization (WHO) histological grade of gliomas, while patients with higher SLP2 expression levels had an overall shorter survival time compared to patients with a lower expression of SLP2 [ 24 ]. It was also demonstrated that the silencing of SLP 2 gene expression could drastically reduce the migration and invasive ability of glioma cells by inhibiting the transcriptional activity of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and repressing the expression levels of NF-κB target genes, including matrix metallopeptidase 9 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%